Trade union action in Algeria: From freedoms to restrictions 1989-2019 - Farid, Hassini; Mechta, Yassine (The International tax journal, 2025)
Trade unions emerged around the world as a reaction to the deteriorating social and economic conditions of the working class, a result of the dire and harsh conditions experienced by societies during that period. The first trade union representations emerged in the form of trade union federations in Britain during the 1720s, the cradle of economic transformation and the development in the level of work by replacing traditional manual work with industrial machines, despite the fact that the workers protested against the harsh working conditions and the long working hours, which exceeded 18 hours a day, in order to obtain compensation that was neither sufficient nor satisfactory. The fever of chaos and protests spread throughout all European countries, such as France and Germany, which are major industrial and economic countries. Then the demands expanded to the various colonies of these countries, demanding that governments change and find solutions to raise the standard of living of the working classes and their purchasing power in order to confront the poverty and diseases prevalent in these countries. This made resorting to labor blocs in the form of unions to defend the rights of the working class inevitable.